Worldwide compendium of mangrove-associated aquatic specieas of economic importance - Matthes, H. (FAO, 1988)
The objective of the compendium is to call attensionto the value of the mangrove ecosystem for fisheries and, in this way, to contribute to the development of interrated management in which the requirements for fisheries and aquaculture are fully recognized.